2022
DOI: 10.1021/acs.inorgchem.2c02604
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Studies of Magnetic Transitions and Spin–Phonon Couplings in the Tetrahedral Cobalt Complex Co(AsPh3)2I2

Abstract: A combination of inelastic neutron scattering (INS), far-IR magnetospectroscopy (FIRMS), and Raman magneto-spectroscopy (RaMS) has been used to comprehensively probe magnetic excitations in Co(AsPh 3 ) 2 I 2 (1), a reported singlemolecule magnet (SMM). With applied field, the magnetic zero-field splitting (ZFS) peak (2D′) shifts to higher energies in each spectroscopy. INS placed the ZFS peak at 54 cm −1 , as revealed by both variable-temperature (VT) and variable-magnetic-field data, giving results that agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…Complete active space self-consistent field (CASSCF) followed by second-order N-electron valence perturbation theory (NEVPT2) was carried out on model complexes with an active space of CAS­(7,5) to compute the spin-Hamiltonian parameters (Table S7, S8, SI). This methodology has been widely used to compute the spin-Hamiltonian (SH) parameters in various open-shell transition metal complexes. , NEVPT2 (CASSCF) computed D values are −29.6(−32.8) cm –1 and −31.6(−34.8) cm –1 for complexes 1 and 2 respectively. The computed E / D values are 0.05(0.06) and 0.04(0.04) for complexes 1 and 2 , respectively, at the NEVPT2­(CASSCF) level of theory (Table , Figure S9, SI).…”
Section: Resultsmentioning
confidence: 99%
“…Complete active space self-consistent field (CASSCF) followed by second-order N-electron valence perturbation theory (NEVPT2) was carried out on model complexes with an active space of CAS­(7,5) to compute the spin-Hamiltonian parameters (Table S7, S8, SI). This methodology has been widely used to compute the spin-Hamiltonian (SH) parameters in various open-shell transition metal complexes. , NEVPT2 (CASSCF) computed D values are −29.6(−32.8) cm –1 and −31.6(−34.8) cm –1 for complexes 1 and 2 respectively. The computed E / D values are 0.05(0.06) and 0.04(0.04) for complexes 1 and 2 , respectively, at the NEVPT2­(CASSCF) level of theory (Table , Figure S9, SI).…”
Section: Resultsmentioning
confidence: 99%
“…The ground state ϕ 1,2 are mostly M S = ±1/2 which are mixed with M S = ±3/2, as a result of x ≠ y in 1 (i.e., rhombic ZFS parameter E). In other transition metal complexes such as Co(AsPh 3 ) 2 I 2 35 not discussed in this article, the ϕ 1,2 and ϕ 3,4 levels are reversed of that in (a), as its D < 0. That is, ϕ 3,4 is the ground level, while ϕ 1,2 is the excited level.…”
Section: Introductionmentioning
confidence: 77%
“…[107][108][109][110][111][112]115 We have sought to probe spin-phonon coupling by spectroscopies. 31,33,35,53,54,124 This article discusses our recent efforts to use a combination of far-IR and Raman magneto-spectroscopies (FIRMS and RaMS, respectively), and inelastic neutron scattering (INS) to study magnetic anisotropies 31,33,35,40,[53][54][55][124][125][126][127] and spinphonon couplings in metal complexes, determining magnetic excited states and coupling constants. Sometimes, the combined use of FIRMS with high-field EPR (HFEPR) leads to the determination of spin-Hamiltonian parameters D, E and g for transition metal complexes.…”
Section: Dalton Transactions Frontiermentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reaction between 1-As and CoBr 2 , a turquoise κ 2 - As , As -chelate complex ( 3-Co , λ max = 777, 680, and 649 nm) with an uncoordinated alkyne moiety was isolated (see Scheme ) and its structure was ascertained by single-crystal X-ray diffraction (see Figure ). As expected for the nearly tetrahedral cobalt ion in 3-Co (τ 4 = 0.87), an effective magnetic moment of μ eff = 4.58 μ B was determined in CD 2 Cl 2 (Evans method), indicative of the S = 3/2 ground state . This interpretation was confirmed by DFT studies, that is, the hypothetical doublet state ( S = 1/2) was found to be higher in energy by 19.8 kcal/mol in comparison to the quartet state (see the Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%